Rancang Bangun Aplikasi Manajemen Layanan Kesehatan (Klinik) Berbasis Website dengan Metode Agile - An Nisa Dira; Andre Farhan Saputra; Nixon Milo Hamonangan (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
The rapid advancement of technology today has an impact on the development of knowledge that is so fast and broad, both in terms of aspects of education, employment, and others, one of which is in the health sector. One of the information technologies that support the management of health services is the application of health service management which is useful for supporting the achievement of order in terms of the administration of health service providers to be successful as expected. The case study in this research is a clinic that does all activities manually, so it tends to require more time and effort. Without access to web-based applications, it is difficult to collect and analyze operational data holistically, which can reduce a clinic's ability to make fact-based decisions and improve overall performance. The solution is a web-based clinical application, with the main goal of facilitating the management of a clinic internally. The making of this application uses an agile method. The steps of this method are data collection, making system requirements analysis, database design, testing, and implementation. This research resulted in the design of this application which includes clinical data management, polyclinic, doctor and staff data, medicines and consumables, and stock management.